(untitled) (Proceedings of International Conference on Special Education, 2015)
This study examines eduplay, an educational form of play with Chinese characteristics, as a means of promoting social competence in early childhood. Although the policies of the Hong Kong government increasingly require a play-based curriculum, many teachers and parents believe that play will detract from academics. Eduplay is a method of learning by playing, an approach that may be more acceptable to teachers and parents in Hong Kong. Results from an experimental study of preschools are presented, showing that eduplay was successful in reducing two problem behaviors, namely clinging and demanding attention. These results have implications for incorporating meaningful play into a play-based curriculum.